Experiences of the implementation of a tool for lifestyle intervention in primary health care: a qualitative study among managers and professional groups - Lindberg Malou; Andersson Agneta; Carlfjord Siw (BMC, 2011)
Abstract Background In recent years there has been increasing interest in transferring new knowledge into health care practices, a process often referred to as implementation. The various subcultures that exist among health care workers may be an obstacle in this process. The aim of this study was to explore how professional groups and managers experienced the implementation of a new tool for lifestyle intervention in primary health care (PHC). The computer-based tool was introduced with the intention of facilitating the delivery of preventive services. Methods Focus group interviews with staff and individual interviews with managers at six PHC units in the southeast of Sweden were performed 9 months after the introduction of the new working tool. Staff interviews were conducted in groups according to profession, and were analysed using manifest content analysis. Experiences and opinions from the different staff groups and from managers were analysed. Results Implementation preconditions, opinions about the lifestyle test, and opinions about usage were the main areas identified. In each of the groups, managers and professionals, factors related to the existing subcultures seemed to influence their experiences of the implementation. Managers were visionary, GPs were reluctant, nurses were open, and nurse assistants were indifferent. Conclusion This study indicates that the existing subcultures in PHC influence how the implementation of an innovation is perceived by managers and the different professionals. In PHC, an organization with several subcultures and an established hierarchical structure, an implementation strategy aimed at all groups did not seem to result in a successful uptake of the new method.